Thermal runaway process in lithium-ion batteries: A review - Yixin Dai; Aidin Panahi (Next Energy)
Climate change and global warming represent critical challenges for the 21st century, partly attributable to the combustion of fossil fuels. The adoption of alternative energy sources presents viable solutions to mitigate these challenges. Among the strategies to address climate change, lithium-ion batteries (LIBs) have emerged as increasingly important. However, the advancement of LIB technology is hindered by the phenomenon of thermal runaway (TR), which constitutes the primary failure mechanism of LIBs, potentially leading severe fires and explosions. This review provides a comprehensive understanding of the TR mechanisms in LIBs, which vary significantly depending on the battery’s materials. Extensive research has been conducted on the component materials of LIBs, the causes triggering TR, and the mechanisms underlying TR in laboratory settings. Yet, further research to fully understand and mitigate TR is necessary as it is a highly complex process that is readily influenced by both external conditions and internal reactions. For LIBs composed of different materials, the processes and mechanisms underlying TR exhibit significant variations. Therefore, this review emphasizes the need to study various battery cells to gain a comprehensive understanding of the TR mechanisms. The focus of this review lies in elucidating the diverse TR mechanisms, preventive methods, and highlighting recent key progresses in research aimed at improving the safety of LIBs. Finally, this review concludes with recommendations for future research and development on the safety of LIBs, emphasizing the need for a more coherent view of TR mechanisms and LIB safety.